Predicting negative human-tiger (Panthera tigris) interactions in mosaic landscapes around Dudhwa and Pilibhit tiger reserves in India - Chatterjee, Mayukh; Chatterjee, Nilanjan; Chandel, Poonam; Bhattacharya, Tapajit; Kaul, Rahul (Frontiers in Conservation Science, 2022)
Negative interactions between humans and large carnivores like tigers (Panthera tigris) and leopards (Panthera pardus) are of concern for the conservation of these carnivores, as well as for the health and wellbeing of people who experience such interactions routinely. Such interactions not only lead to human deaths, injuries and loss of domestic animals, but also can result in retaliatory persecution of carnivores and cause their population declines. The Dudhwa-Pilibhit landscape in the northern Indian state of Uttar Pradesh is popularly regarded to be the second most affected hotspot of human-tiger conflicts in the country. Yet, very little information is published on human-tiger conflicts in this landscape. In this study, we recorded 7.4 ± SD5.8 (range: 1-20) negative interactions per year between people and tigers that led directly to human deaths and injuries. Although there appeared to be peaks in negative interactions in more recent years, these were found to be statistically non-significant. The peaks in the numbers of cases in 2009-10 and 2016-17 can be attributed to higher numbers of human casualties cause by individual ‘problem’ tigers, and not due to an increase in the number of tigers engaging in conflicts. We used binomial generalized linear modelling to model the risk to humans from being attacked by tigers depending on landscape characteristics. This approach demonstrated that the mosaics of forests and human settlements, especially the presence of agriculture, forest patches and waterbodies, were the predominant factors at play. Notably, higher risks were not mediated by the presence of larger cattle population. Proximity of villages to forests or natural vegetation patches was the most significantly contributing factor identified by the model output. This suggested that despite the prevalent perception of attacks on humans occurring in human-dominated areas of this landscape, areas with forests or other natural vegetation entailed higher risks. This was corroborated by field observations, with most attacks occurring within, or close to, forests or dense vegetation. Based on these findings, we recommend that restricting human movements and taking precautionary measures in high-risk areas can significantly reduce negative interactions with tigers in our study area.